Urbanisation Pattern of Incipient Mega Region in India - Ramachandra, T. V.; Aithal, Bharath H.; Beas, Barik (TeMA - Journal of Land Use, Mobility and Environment, 2014)
<!–[if gte mso 9]> <![endif]–> The focus of the current study is to analyse the spatial patterns of urbanisation and sprawl in Pune city using temporal remote sensing data